Corneal arcus and its associations with ocular and general parameters: the central India eye and medical study - Vurgese, Sujiv; Panda-Jonas, Songhomitra; Saini, Nandita; Sinha, Ajit; Nangia, Vinay; Jonas, Jost B. (Investigative ophthalmology & visual science, 2011)
To investigate the prevalence of corneal arcus and its associations. The Central India Eye and Medical Study was a population-based study performed in rural Central India on 4711 subjects (age, 30+ years). Corneal arcus was assessed in corneal photographs. The study included 952 randomly selected participants. Mean body mass index (BMI) was 19.8 ± 3.6 kg/m2, with 786 (41.3%) subjects being underweight (BMI < 18.5 kg/m2). Corneal arcus of any degree was detected in 102 (10.7% ± 1.0%; 95% CI, 8.8-12.7) subjects. Corneal arcus was significantly associated with increasing age (P < 0.001). It was not significantly (all P > 0.10) associated with serum concentrations of high-density lipoproteins, cholesterol, creatinine, glucose, and glycosylated hemoglobin; with prevalence of arterial hypertension and diabetes mellitus; with body height, weight, and BMI; or with level of education, daily activities, nutrition, alcohol consumption, smoking, and blood pressure. In an intereye comparison, corneal arcus was significantly more marked in the eye with lower intraocular pressure (P = 0.006), thinner central cornea (P = 0.005), and more hyperopic refractive error (P = 0.003). In this adult rural Central Indian population with low mean BMI, the prevalence of corneal arcus was 10.7% ± 1.0%. The only systemic parameter associated with corneal arcus was increasing age (P < 0.001). Corneal arcus was not associated with dyslipidemia, diabetes mellitus, arterial hypertension, alcohol consumption, or smoking. In this population with low BMI, corneal arcus was not a clinical biomarker for major metabolic disorders. The intereye associations between corneal arcus and low intraocular pressure, thin central cornea, and hyperopia may be of importance in the ophthalmic examination.
Gesehen am 03.11.2022